A possible case of sporadic aurora observed at Rio de Janeiro - Oliveira, Denny M.; Hayakawa, Hisashi; Bhaskar, Ankush; Zesta, Eftyhia; Vichare, Geeta (My University, 2020)
Being footprints of major magnetic storms and hence major solar eruptions, mid- to low-latitude aurorae have been one of the pathways to understand solar–terrestrial environments. However, it has been reported that aurorae are also occasionally observed at low latitudes under low or even quiet magnetic conditions. Such phenomena are known as “sporadic aurorae”. We report on a historical event observed by a scientist of the Brazilian Empire in Rio de Janeiro on 15 February 1875. We analyze this event on the basis of its spectroscopic observations, along with its visual structure and coloration, to suggest this event was a possible case of sporadic aurorae. Given the absence of worldwide aurora observations on that day as a consequence of low magnetic activity recorded on the days preceding the observation, in addition to a detailed description, the event observed can most likely be classified as a sporadic aurora. We discuss the geographic and magnetic conditions of that event. Thus, we add a possible case of sporadic aurora in the South American sector.
Keywords: Space weather; Sporadic aurora; Analysis of historical data